Píctures and poems: a synthesis of methodological reflexion on the works of Luis Feíto - García Berrio, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
The goal of this papel' is to illustrate a case of the strong equivalencies existing between two different kinds of the artistic discourse: the literary and the plastic one. Proceeding along the differents steps of the so called "semiotic scheme", this research shows in a modern scientific way, the parallelism between poetry and painting, illustrated by the analysis Luis Feito's paintings, one of the most promineal spanish modern artists.
Keywords: poetry and painting; Luis Feito; methodology